Knowledge, Stress, and Treatment Compliance among Hypertension Clients in Rural Areas - Lisa Tiyansi; Dewi Hartinah; Muhamad Jauhar; Novi Tiara (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2026)
Hypertension is a major risk factor for increasing mortality and morbidity rates. This is supported by the increasing prevalence of hypertension cases every year worldwide. If blood pressure cannot be controlled, it will lead to complications such as stroke, retinopathy, heart failure, heart attack, kidney failure, and disability. Therefore, adherence to treatment is crucial to prevent these complications. However, in the treatment of long-term diseases such as hypertension, which require lifelong treatment, barriers to medication adherence often occur. The purpose of this study was to analyze the relationship between knowledge and stress with medication adherence in hypertension patients in rural areas. The study design used correlation analysis with a cross-sectional approach. The independent variables were knowledge and stress, while the dependent variable was medication adherence. This study was conducted in two villages in Kudus Regency, which is the locus of hypertension, in April 2025. The study sample consisted of 97 respondents selected through a cross-sectional approach through purposive sampling based on inclusion and exclusion criteria. The instruments used include the Hill-Bone Compliance to High Blood Pressure Therapy Scale, the Hypertension Knowledge-Level Scale, and the Perceived Stress Scale (PSS-10). Data analysis using the chi-square test. The results of the study showed a significant relationship between knowledge (p=0.000) and stress (p=0.000) with medication adherence. Knowledge and stress are associated with medication adherence in hypertensive clients. Community health centers need to implement innovative programs to improve medication adherence through structured health education and stress management.